Agricultural Science and Technology Indicators (ASTI): Evaluation of outcomes based on the use of ASTI, 2008–2018 - Lowder, Sarah K. (International Food Policy Research Institute, 2019)
This is the final report for an evaluation of the use of one of the flagship programs of the International Food Policy Research Institute (IFPRI): the Agricultural Science and Technology Indicators (ASTI). In addition to identifying who has used ASTI and how, this report aims to go a step further and examine outcomes. An outcome may be defined as “a change in knowledge, skills, attitudes and/or relationships, manifest as a change in behavior, to which research outputs and related activities have contributed” (CGIAR MEL CoP 2018). In the CGIAR Program on Policies, Institutions, and Markets (PIM) context, the outcomes are usually changes in policies, programs, or investments. The recognition or use of outputs by partners in decision making or capacity strengthening can also be considered as an early, less mature, outcome. We first review previous reports that evaluated ASTI work. Then we describe the methods used for this study to develop an evidence base for ASTI outcomes. We summarize results from stakeholder surveys, citation searches, and downloads. Next, we present results from the survey of authors who have cited ASTI work.